Effect of Microparticle Crystallinity and Food Matrix on the Release Profile and Antioxidant Activity of Encapsulated Gallic and Ellagic Acids During Simulated in Vitro Intestinal Digestion - Gimenez-Castillo, B (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
The development of phenolic-based functional food ingredients is of growing interest due to their beneficial effects on human health. This study investigated the combined influence of microparticle physical state, phenolic compound type (gallic acid, GA; and ellagic acid, EA), and model food matrix on the release profile, bioaccessibility, and antioxidant activity of GA and EA during in vitro gastrointestinal digestion. GA and EA were encapsulated with inulin (In) by spray-drying. By varying formulation and operational conditions, both semicrystalline (GA-InSc, EA-InSc) and amorphous (GA-InA, EA-InA) microparticles were obtained. Microparticles were characterized for crystallinity, encapsulation efficiency, particle size, morphology, and release profile during in vitro simulated gastrointestinal digestion following the INFOGEST method. The physical state of microparticles and type of phenolic compound critically influenced release profile, bioaccessibility, and antioxidant activity during digestion. GA, being more water-soluble, was rapidly released, reaching nearly 100% in the gastric phase, whereas EA exhibited limited gastric release and higher intestinal release, particularly in EA-InSc. Incorporation into different food matrices further modulated these effects; carbohydrate- and blend-based matrices improved phenolic release and antioxidant activity for both compounds. These findings highlight the importance of microparticle formulation, phenolic characteristics, and matrix interactions in designing functional food ingredients with optimized health benefits.